Hellenistic science and culture in the last three centuries B.C. - Sarton, George (Dover Publications, 1959)
The book is divided into two parts: Part One deals with the third century B.C. As the empire of Alexander the Great disintegrated, a Greek intellectual hegemony evolved, grounded in the work of Ptolemy and Euclid, Aristarchos and Archimedes, Eratosthenes and other thinkers. Ranging widely across the spectrum of Hellenistic accomplishment, Dr. Sarton outlines advances in geography and chronology, physics, technology, anatomy, medicine, philosophy and religion, language and more.